Development of the Overload Protection Device for Mechanical Linear Actuator - Wang, Pei-Yu; Cai, Ren-Hao (Recent Patents on Mechanical Engineering, 2011)
Linear actuators are widely adopted in a variety of life industries, including hospital beds with automatic lifting mechanism, conveyors, automatic doors and windows, adjustable computer tables, and leisure equipments. The need for more efficient product classification for manufacturers and the demand for product safety for users are two major issues currently that the design of linear actuators encounters. The main purpose of this study is to apply a complete engineering design process to design the overload protection device for mechanical linear actuator. In addition to shortening the timeline for product design, improved design processes can increase the value-added of the products and enhance international competitiveness. By searching domestic and overseas patents and synthesizing them into a summary table of patent analysis, linear actuators and clutches are clearly analyzed to produce a patent map. Then quality function deployment (QFD) is employed for functional decomposition, project specifications decision making, concept examination, and finally product sampling and testing. The most important design point in product development is to understand the existing value of those functions. With this idea, through concept examination, the calculation of mechanics is used to conduct a detailed design.
Keywords: QFD